Measuring the attitudes of the students of the geographic departments at the University of Basra towards the environment and development. Environment (Build and Apply) (Journal of the College of Basic Education, 2023)
The escalation of the economic activity of human societies in recent years has created a direct impacton the environment, as man annually takes from the environment huge amounts of natural resources and recycles them andTreating it so that tons of waste, excrement and pollutants return to the environment, which cause severe effects.importance on the components of the environment and their quality, and this negative impact on the components of the environment leaves its effectsHarmful to human life and future, causing pollution, disease and famine. that manyPeople do not understand the problems of the environment or its impact. Rather, many students do not know the problems.environment, and they do not have positive attitudes towards it, just as the curricula of social sciences, foremost of which is scienceGeography, as an environmental science, cannot develop the environmental conscience among students, nor does it inform them of the importance ofsustainable development in solving environmental problems. Therefore, the problem of the current research is to build a toolTo measure students' attitudes towards the environment and environmental development, and to find out the extent to which students are familiar with the problems ofthe environment and how to solve it.